TRANSFORMATION OF CONSCIOUSNESS UNDERSTANDING IN THE INTERNET ERA - A. I. Ponomarev (Дискурс, 2016)
The article contains analysis of how the Internet can help us to understand better what consciousness is. The Internet analysis can be useful in answering some questions of contemporary analytical philosophy of mind, namely collective mind, artificial intelligence, first person perspective and personal identity.